Działalność gospodarcza katolickich szkół wyższych - Kiraga, Joanna (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2019)
In reference to Catholic schools, apart from the general regulations, special canonical regulations are also applied. The dual legal regime affects the position of Catholic schools, which, in addition to the mission related to educating students, are to promote patterns of Christian behavior and values. In order to raise funds for educational and religious activities, Catholic schools, especially when it comes to universities, undertake economic activity. The position of Catholic universities as entrepreneurs differs from the situation of other participants in business transactions. The article discusses the legal position of Catholic universities as entrepreneurs and the forms of economic activity carried out by schools. The analysis intends to conclude that, due to the guaranteed constitutional equal treatment of entities, including entrepreneurs, it is necessary to take legislative action that would constitute the implementation of the above principle in the field of economic activity performed by Catholic universities.
Keywords: entrepreneur; education; dual legal order; public interest; business operations